Constructing Tissue-Engineered Dressing Membranes with Adipose-Derived Stem Cells and Acellular Dermal Matrix for Diabetic Wound Healing: A Comparative Study of Hypoxia- or Normoxia-Culture Modes - Wen Zhou; Xin Zhao; Xin Shi; Can Chen; Yanpeng Cao; Jun Liu (Stem Cells International)
Diabetes foot ulcer (DFU) is a serious complication of diabetes, characterized by impaired vascular function, limited angiogenesis, and chronic inflammation. Direct stem cell injection on treating DFU is far from satisfactory in clinical practice, as this therapy neither protects nor localizes the injected cell suspension at the chronic ulcer site. Meanwhile, most of injected cells gradually perished within several days due to senescence or apoptosis. Acellular dermal matrix (ADM) has the potential to act as excellent cell delivery vehicles, considering it is highly biomimetic to native dermal tissue, has low immunogenicity, and suitable for stem cell attachment and proliferation. Hypoxia culture has significantly enhanced effects on the survival ability of in vitro cultured stem cells, indicating this culture mode is a suitable way for inhibiting the senescence or apoptosis of transplanted cells. In the current study, we, respectively, culture adipose-derived stem cells (ADSCs) on an ADM membrane under a hypoxia or normoxia condition to construct two kinds of tissue-engineered dressing membranes (H-ADSCs/ADM and N-ADSCs/ADM) and then comparatively evaluated their efficacy on DFU healing using a diabetic rat model. In vitro results showed that hypoxia precondition could stimulate the ADSCs secreting VEGF-A, and the culture medium from hypoxia-preconditioned ADSCs could enhance the proliferation, migration, and angiogenesis of HUVECs. In vivo results indicated that compared to the N-ADSCs/ADM membrane, the transplanted cells in the H-ADSCs/ADM membrane can survive longer at the chronic ulcer site, consequently improve angiogenesis, inhibit inflammation, and increase extracellular matrix remodeling, eventually accelerating DFU closure. This study provides an innovative covering graft for the treatment of DFU in the clinic.